2020
DOI: 10.3390/plants9060725
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Phytohormones on Morphology, Yield and Cannabinoid Content of Cannabis sativa L.

Abstract: The impact of exogenously applied plant growth regulators (PGR), 1-naphthalenaecetic acid (NAA), 6-benzylaminopurine (BAP), and a mixture of both (NAA/BAP-mix), was investigated in regard to plant height, length of axillary branches, number of internodes, biomass yield and cannabinoid content of three different phytocannabinoid-rich (PCR) Cannabis genotypes. The results showed that total plant height was significantly reduced under the application of NAA (28%), BAP (18%), and NAA/BAP-mix treated plants (15%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…To ensure the needed high quality standards for medical and pharmaceutical products, it is necessary to scientifically develop and evaluate cultivation methods. Recently, there has been an increased focus on arbuscular mycorrhiza [ 7 ], cultivation substrates [ 8 , 9 ], plant density [ 10 ], phytohormones [ 11 ] and the effect of fungal pathogens [ 12 ] to further develop cultivation systems.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the needed high quality standards for medical and pharmaceutical products, it is necessary to scientifically develop and evaluate cultivation methods. Recently, there has been an increased focus on arbuscular mycorrhiza [ 7 ], cultivation substrates [ 8 , 9 ], plant density [ 10 ], phytohormones [ 11 ] and the effect of fungal pathogens [ 12 ] to further develop cultivation systems.…”
Section: Introductionmentioning
confidence: 99%
“…The cannabinoid extraction was performed according to Burgel et al [28]. Quantitative analysis of cannabinoids, particularly cannabidiol (CBD), cannabidiolic acid (CBDA), ∆ 9 -tetrahydrocannabinol (THC) and tetrahydrocannabinolic acid (THCA), was performed, according to the HPLC methods of Lehmann and Brenneisen [29] with slight modifications after Burgel et al [30].…”
Section: Extraction and Quantification Of Cannabinoids By Hplc Analysismentioning
confidence: 99%
“…Previous studies in other plant species revealed that different tissues and different environmental conditions would require unique reference genes to accurately interpret the expression of speci c genes 35,36 . Eleven different conditions including osmotic stresses, heavy metal stresses, plant hormone stimulus, and UV light application were reported to affect the cannabinoid synthesis 37,38,39,40 . Results obtained in this study from four programs: geNorm, NormFinder, BestKeeper, and RefFinder were not consistent, particularly BestKeeper which was much more distinct from the other software methods.…”
Section: Discussionmentioning
confidence: 99%